Synthesis of ZnO–ZnCo2O4 hybrid hollow microspheres with excellent lithium storage properties. (1st July 2015) - Xie, Qingshui; Zeng, Deqian; Ma, Yating; Lin, Liang; Wang, Laisen; Peng, Dong-Liang
Graphical abstract: Highlights: Well-dispersed ZnO–ZnCo2 O4 hybrid hollow microspheres are prepared for the first time. ZnO–ZnCo2 O4 hybrid hollow microspheres exhibit greatly enhanced lithium storage properties. The unique structural features of hybrid microspheres account for their superior electrochemical properties. Abstract: ZnO–ZnCo2 O4 hybrid hollow microspheres are successfully produced via an annealing process of the pre-fabricated zinc–cobalt citrate hollow microspheres in air. ZnO and ZnCo2 O4 have homogeneous distribution within the whole hollow microspheres. The gained hybrid hollow microspheres deliver outstanding lithium storage properties when utilized as the anode material in lithium ion batteries. A high reversible capacity of 1199 mA h g −1 can be retained after 200 cycles. The exceptional electrochemical properties of the hybrid hollow microspheres are ascribed to the synergetic effect between ZnO and ZnCo2 O4 nanoparticles, the catalytic effect of Co nanocrystals, the favorable hollow structures together with the nanometer-sized building blocks of hybrid microspheres.